Assessment of cryptocurrencies as an asset class by their characteristics - Thomas Ankenbrand; Denis Bieri (Investment Management & Financial Innovations, 2018)
The cryptocurrency market has witnessed significant growth in the past few months. The emergence of hundreds of new digital currencies and the huge increase in the prices of their leading representatives have attracted a lot of attention from investors. However, the financial characteristics of the cryptocurrency markets have not been systematically evaluated yet. As a consequence, there is currently no consensus on whether cryptocurrencies constitute an individual asset class or if they share substantial similarities to stocks, bonds, commodities or foreign exchange. Based on Markowitz et al. (2017) this paper aims to fill this lack of research by evaluating the cryptocurrency market based on seven requirements of an individual asset class. The authors find that the cryptocurrency market distinguishes itself remarkably from established asset classes in terms of risk and return. Additionally, the low correlation between the cryptocurrency markets and these established asset classes induces a diversification potential for investors, leading to more favorable risk/return profiles of their portfolios. But also the emergence of investment services and products provided by the financial industry and the increasingly cost-effective access to cryptocurrencies corroborate the conclusion that cryptocurrencies can be seen as an individual asset class.